Значение дыма в ритуале кровавого жертвоприношения - Нестан Ратиани (ՀՀ ԳԱԱ հրատ.)
All lives belong to God. It comes from him and to him it returns, and when he wants it he takes it. But it differs otherwise from true sacrifice where man makes an offer of his own accord. Since in most sacrifices men eat the carcass of the victim, what is God supposed to receive? We hypothesize that burning of the victim was an important and necessary part in the rituals of blood sacrifice.
Keywords: G Geography; Anthropology; Recreation; GR Folklore